U.S. Tariff Policy and the Joint Reaction of Indonesia’s Stock and Gold Markets - Wefielananda, Rahmi Afzhi; Andriani, Yessy; Azry, Said Maulana (Jurnal Ilmiah Multidisiplin Indonesia (JIM-ID), 2025)
The United States exerts a substantial influence on the global economy. Its trade policies not only directly affect its trading partners but also generate broader multiplier effects across other national economies. This study examines the impact of the reciprocal tariff policy announced by the United States government in February 2025 on stock and gold prices in Indonesia. Using the Three-Stage Least Squares (3SLS) method, the results show that the tariff policy significantly influences both variables. Gold prices respond positively two weeks after the tariff announcement, while stock prices react negatively in the same week, rebound in the following week, and decline again in the second week. Furthermore, changes in gold prices significantly affect stock prices at the fourth lag, whereas changes in stock prices have no significant effect on gold prices. These empirical findings are consistent with the Efficient Market Hypothesis, Rational Expectations Theory, the Hedging and Safe Haven Asset Hypothesis, and the Asset Substitution Hypothesis. Overall, the study demonstrates that Indonesian investors respond rationally to global policy changes in line with financial market dynamics.